Comparación de la composición corporal obtenida por bioimpedancia e hidrodensitometría en mujeres de 38 a 60 años de Medellín-Colombia (2015)
ABSTRACT: Body composition assessment by bioimpedance is non-invasive, inexpensive and portable. Objective: To assess the validity of bioimpedance to estimate fat mass percentage (%FM) in women. Materials and methods: This is a cross-sectional study with a sample of 50 women, 38 to 60 years old. Hydrodensitometry with simultaneous measurement of the lung residual volume was used as the reference method. The %FM was assessed by the bioimpedance hand-to-feet technique using the equations of Sun and Kotler. A Tanita body composition scale was used to estimate the %FM with the bioimpedance feet-to-feet technique. Results: The %FM estimated by Sun (34,0±4,8) and Kotler (34,4±6,0) were not different (p>0,05) from the %FM obtained by hydrodensitometry (33,3±5,6). The %FM estimated by Tanita differed from the reference method (30,1±5,8, p=0,000). BIA equations and Tanita showed low agreement with hydrodensitometry: Sun (Bland-Altman: -0,73 CI95%: -9,9; 8,4), Kotler (Bland-Altman: -1,1 CI95%: -10,7; 8,5) and Tanita (Bland-Altman: 3,2 CI95%: -5,8; 12,2). Conclusions: In this specific population of women, hand-to-feet bioimpedance with Sun and Kotler equations accurately estimated the %FM of the whole group, but these equations lacked validity to assess the individual %FM. The Tanita body composition scale lacked validity to assess both; individual and group %FM.